Conditional Cash Transfers and Labor Market Conditions - Teresa Molina; Joaquim Vidiella-Martin (Institute of Labor Economics (IZA), 2021)
Do local labor markets influence the effectiveness of educational policies? To answer this question, we focus on Mexico's conditional cash transfer program, PROGRESA, documented to have increased educational attainment. We show that PROGRESA's impact on schooling was smaller in areas with more export-oriented manufacturing jobs and argue this is because these jobs generate more convex opportunity costs of schooling. Consistent with this, the heterogeneity we document is strongest among those old enough to be working in factory jobs. In addition, this heterogeneity is primarily driven by jobs that directly influence schooling opportunity costs: low-wage jobs and jobs for school-aged workers.
Keywords: I28; F16; I38; O14; 330; conditional cash transfers; export manufacturing; Mexico; opportunity costs